Effects of lycium and lycium-composed formula on the peripheral coldness induced by local cooling in mice - Jian-Rong Zhou; Bunka Ishikawa; Mihoko Nakashima; Kazumi Yokomizo (International Journal of Phytomedicine, 2016)
Recently people appealing for peripheral coldness increase. Lycium fruits have a long tradition of use in nutrition and traditional medicine in East Asia, while its effect on peripheral coldness is not yet investigated. We study the effects of lycium and lycium-rich formula (Ligustrum lucidum ait, LLA) on the peripheral coldness induced by local cooling in mice. 7-week old male ddY mice were administered either water (control) or lycium or LLA for 2 weeks. After an aesthesia, the mouse body except for head was immersed into 10 ℃ water for 10 min. Then the skin surface and rectal temperature of mouse were measured with a thermocamera and a thermocouple thermometer, respectively. And two laser Doppler flow probes were set to measure the skin blood flow of plantar and tail, respectively. In the case of 1-week administration on mice, 10% lycium- and 10% LLA-treatments showed good recovery of whole body surface temperature measured by a thermocamera. After 2-week administration on mice, there were not significant differences in the recovery rates of rectal temperature compared with those of the control group. And the 30 min- and 50 min-recovery rates of dorsal skin surface temperature by 1% and 10% lycium-treatment were significantly higher than those of the respective control. Further, the 30 min- and 50 min-plantar skin blood flow by 10% LLA-treatment were significantly higher than those of the respective control. The 50 min-tail skin blood flow by 10% LLA-treatment and 60 min-tail skin blood flow by 1% LLA-treatment were significantly higher than those of the control, respectively. It can be concluded that the administration of lycium or LLA on mouse led to an increase of peripheral blood blow, and thus a recovery of skin surface temperature.